2022
DOI: 10.7759/cureus.22847
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Computed Tomography Severity Score With Patient Characteristics and Survival in Hypoxemic COVID-19 Patients

Abstract: BackgroundComputed tomography (CT) scans and CT severity scores (CTSS) are widely used to assess the severity and prognosis in coronavirus disease 2019 . CTSS has performed well as a predictor in differentiating severe from non-severe cases. However, it is not known if CTSS performs similarly in hospitalized severe cases with hypoxia at admission. MethodsWe conducted a retrospective comparative study at a COVID-care center from Western India between 25th April and 31st May 2021, enrolling all consecutive sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease. Moreover, this may provide a high-impact tool to enhance awareness of the severity of COVID-19 pneumonia [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease. Moreover, this may provide a high-impact tool to enhance awareness of the severity of COVID-19 pneumonia [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning D dimer, an average of 320 ug/L was obtained in the Egyptian study [23] and 434 ug/L in the Indian study by Yanamandra [30], values well below those found in Huancayo where the average D dimer was 1295 ug/L in mild cases. The Egyptian study's patients with severe tomographic pulmonary compromise had an average D-dimer of 1210 ug/L.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, in the Indian study its average value was 29 mg/dL, values much lower than those found in our population, in which patients with mild compromise had an average of 69.8 mg/dL of C-reactive protein. The moderate cases of the study from India [30] had an average CRP of 66.6, which was even below the values of the mild cases from Huancayo, where the patients with moderate involvement had an average C-reactive protein of 130.5. mg/dL.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“… 35 Admission hyperglycemia, elevated d-dimer, and high HRCT score are potential risk factors for adverse outcomes and death. 34 , 36 Shang et al, demonstrated that the incidence of respiratory failure (p-0·022), acute cardiac injury (p < 0·01), and death (p-0·001) in the diabetes group was significantly higher than that in the non-diabetes group. 32 Another study done by Chen et al, in China showed C-reactive protein might help identify patients with diabetes who are at greater risk of dying during hospitalization (p-0·043).…”
Section: Discussionmentioning
confidence: 99%